MRI Accuracy in Diagnosing Sonographically Indeterminate Masses Taking Histopathology as Standard - Iram Iqbal; M. Awais Farooq; Sadaf Arooj; Yasir Qavi; Rukhsana Nasim; Sehrish Zafar (Proceedings, 2024)
Introduction: Approximately 25% of ultrasound-detected adnexal masses pose clinical challenges, being indeterminately categorized as benign or malignant. Characterizing them is pivotal for deciding surgery or pelvic MRI.